Elaboración de un diagnóstico de la gerencia del proyecto “mantenimiento y rehabilitación de la Carretera Honda – Villeta” (2015)
Road infrastructure projects are frequently criticized by public opinion, because, despite the growth of the sector, there is a precedent of numerous unfinished projects, or that end up without complying with the stipulated scope or They conclude with high cost overruns and overtime. The previous problem is presented by various causes; One of them is the lack of planning for this type of projects, together with the lack of knowledge of adequate management practices. From the academy and through the present work of degree, within the framework of the Specialization in Development and Integral Management of Projects of the Colombian School of Engineering, seeks to strengthen knowledge in this field, in order to feed back to different institutions interested in the execution of road infrastructure projects, through the identification of strengths, threats, weaknesses or opportunities to improve the processes and managerial competences involved during the execution of the project "Maintenance and rehabilitation of the Honda - Villeta highway". Additionally, it is intended to give this academic year the treatment that merits, in general, any project, taking into account its managerial aspects, which are reflected in the development of a Management Plan, in which the application of principles and management tools throughout the life cycle of the Degree Work, for the management of aspects related to its scope, time, cost, quality, communications and risks. The documentation and supports generated during this process are recorded in the Management Book that is attached to this Report.